TIPIT: A randomised controlled trial of thyroxine in preterm infants under 28 weeks' gestation - Victor Suresh; Didi Mohammed; Gamble Carrol; Turner Mark A; Ng Sze M; Weindling Alan M (Trials, 2008)
Abstract Background Infants born at extreme prematurity (below 28 weeks' gestation) are at high risk of developmental disability. A major risk factor for disability is having a low level of thyroid hormone which is recognised to be a frequent phenomenon in these infants. At present it is unclear whether low levels of thyroid hormone are a cause of disability, or a consequence of concurrent adversity. Methods We propose an explanatory multi-centre double blind randomised controlled trial of thyroid hormone supplementation in babies born below 28 weeks' gestation. All infants will receive either levothyroxine or placebo until 32 weeks' corrected gestational age. The primary outcome will be brain growth. This will be assessed by the width of the sub-arachnoid space measured using cranial ultrasound and head circumference at 36 weeks' corrected gestational. The secondary outcomes will be (a) thyroid hormone concentrations measured at increasing postnatal age, (b) status of the hypothalamic pituitary axis, (c) auxological data between birth and 36 weeks' corrected gestational age, (d) thyroid gland volume, (e) volumes of brain structures (measured by magnetic resonance imaging), (f) determination of the extent of myelination and white matter integrity (measured by diffusion weighted MRI) and brain vessel morphology (measured by magnetic resonance angiography) at expected date of delivery and (g) markers of morbidity including duration of mechanical ventilation and chronic lung disease. We will also examine how activity of the hypothalamic-pituitary-adrenal axis modulates the effects of thyroid supplementation. This will contribute to decisions about which confounding variables to assess in large-scale studies. Trial registration Current Controlled Trials ISRCTN89493983